2020
DOI: 10.5761/atcs.ra.19-00310
|View full text |Cite
|
Sign up to set email alerts
|

Is the Use of BIMA in CABG Sub-Optimal? A Review of the Current Clinical and Economic Evidence Including Innovative Approaches to the Management of Mediastinitis

Abstract: worldwide 1,2) with annual volumes of approximately 160000 isolated cases in the US. 3) There is a significant inter-country variation with recent incidence rates ranging from 17 to 73 per 100000 inhabitants in western European countries. 4) The absolute number of CABG has fallen during the last decade due to an increase in percutaneous coronary intervention (PCI) procedures. For example, in Germany, between 2008 and 2018, isolated CABG surgery decreased from 47337 to 33999 cases (-28%). According to current i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Research evidence has shown that using IMA grafts (or ITA grafts) correlates with an elevated risk of SWI, especially when using BIMA [ 6 ]. Research by Grossi et al [ 33 ] demonstrated that having one or more IMA grafts increased the prevalence of sternal infection by 1.37% compared to patients who had no IMA graft in CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research evidence has shown that using IMA grafts (or ITA grafts) correlates with an elevated risk of SWI, especially when using BIMA [ 6 ]. Research by Grossi et al [ 33 ] demonstrated that having one or more IMA grafts increased the prevalence of sternal infection by 1.37% compared to patients who had no IMA graft in CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has described numerous risk factors for SWIs [5]. The use of the bilateral internal mammary artery (BIMA) for coronary artery grafting is the most consistently reported independent risk factor for SWI, together with insulin-dependent diabetes and obesity BIMA use alone can increase the risk by 4.23 times [1,[5][6][7][8][9][10]. This has resulted in the use of BIMA in CABG, despite better long-term prognosis, which has been restricted to low-risk patients [1,6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that RIMA was associated with better long-term outcomes compared to other conduits. 13,14 Goldstone and associates found that RIMA was associated with increased sternal wound infections and offered no advantages over the radial artery. 15 RIMA was also associated with increased operative time, bleeding, and preoperative morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current literature remains confusing and the use of bilateral mammary arterial conduits especially in diabetics, remains rare. 1 Surgeons are hesitant to use BIMA grafts, 2 as over the past 5 years, no growth was seen in BIMA use among Medicare beneficiaries in the USA.…”
Section: Introductionmentioning
confidence: 99%